Risk management and the stated investment costs by independent power producers - Kashi, Bahman (Elsevier Science Bv, 2015)
Evidence presented in this article suggests that in less developed countries the independent power producers (IPPs) have an incentive to overstate the investment cost as an instrument to mitigate the country risk in greenfield electricity generation projects. This technique is an effective risk mitigation strategy under the conventional financing and contractual arrangements in such markets. It, however, promotes the use of less efficient power plants. The distortion in the choice of technology results in economic losses over the life of the plants. The findings of this research have important policy implications that can assist regulatory bodies, governments, and international financing agencies to adopt a more informed approach to the integration of private investment into the electricity generation capacity of developing countries. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: IPP; PPA; Privatization; Power generation; Electricity; Risk management